Agricultural research in Nigeria: the roles of institutional libraries (2001)
Investigates the problems of agricultural research libraries vis-à-vis their effects on the advancement of agricultural research in Nigeria. Proffers solutions in the form of modern electronic information facilities like electronic networking, e-mail and internet access. A method of working is suggested in which research institutes and universities in southwest Nigeria can each selectively develop a database information system on agricultural research, all of which are coordinated through a local area network. This will facilities access to information possessed by other such institutions. The advantages of the model are numberous: reduction of the cost information acquisition, reduction in the duplication of reserch efforts and greater productivity by agricultural research scientist.